PENEGAKAN HUKUM TINDAK PIDANA ILLEGAL LOGGING DI WILAYAH POLISI AIR KABUPATEN BENGKALIS - Yani Ochtavia; Emilda Firdaus; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Illegal logging is a crime against forest damage in the field of forestry. Illegal logging includes illegal logging in a forest area that is illegal or without permission from the government or the authorities. The crime of illegal logging is regulated in Law No. 18 of 2013 concerning Prevention and Eradication of Forest Destruction. This study raises the problem of illegal logging that does not have a permit from the government. The purpose of this research is, first, to discuss how to enforce illegal logging. Second, what are the obstacles in law enforcement for illegal logging. And third, how to overcome law enforcement for illegal logging. The type of research the author will do is to use the juridical socioligical legal research method. This research method uses primary data that is data obtained directly from the field, and also secondary data, namely library research using primary legal materials secondary legal materials, and tertiary legal materials. The data is then used to describe a problem object in the form of synchronizing the facts that occur with the applicable laws and regulations. The results of the study by the author are first, law enforcement or illegal logging has not proceeded smoothly as it should because of the lack of security and supervision of the apparatus, the imbalance in the number of personnel of law enforcement officers. Second, the obstacle faced by the apparatus in enforcing the law of illegal logging is the lack of facilities and infrastructure owned by the Bengkalis Regency Water Pol. Third, efforts to overcome law enforcement on illegal logging by providing and conducting socialization in every village, conducting routine patrols and conducting raids. Keywords: Law Enforcement, Criminal Acts, Illegal Logging.